2020
DOI: 10.1021/acs.iecr.0c00219
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of a Self-Healing, Multiresponsive Color-Change Hydrogel

Abstract: Hydrogels are smart materials with a high moisture content, elasticity, and stimuli to pH and temperature and are widely used in drug delivery, wound dressings, tissue engineering, parting materials, and sensors. However, a hydrogel with a multiresponsive feature is desired and challenging to produce. Here, a novel multiresponsive color-change hydrogel, including pH response, light response, and alcohol response, was successfully fabricated by introducing Michler’s hydrol blue (MHB) into a semicrystalline hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…These defects of traditional stretchable materials severely limit their reliability and shorten the service life. , Motivated by the self-healing of organisms, polymeric materials with self-healable function have been investigated and used to solve the above problems. To endow polymeric materials with a self-healable property, a variety of structural designs, including stimulus response, supramolecular interactions, reversible covalent bonds, , and synergy of multiple dynamic bonds , were constructed. Among them, the synergy of multiple dynamic bonds may be a proper design concept for high-strength and rapid high-efficiency self-healable elastomers …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These defects of traditional stretchable materials severely limit their reliability and shorten the service life. , Motivated by the self-healing of organisms, polymeric materials with self-healable function have been investigated and used to solve the above problems. To endow polymeric materials with a self-healable property, a variety of structural designs, including stimulus response, supramolecular interactions, reversible covalent bonds, , and synergy of multiple dynamic bonds , were constructed. Among them, the synergy of multiple dynamic bonds may be a proper design concept for high-strength and rapid high-efficiency self-healable elastomers …”
Section: Introductionmentioning
confidence: 99%
“…10.1021/acs.iecr.0c05238. The experimental process; the recipe of self-healable elastomers; 1 H NMR and13 C NMR spectra; DSC curves; element detection and EDS; stress−strain curves; the image of the molecular structure; stress relaxation curves; self-healable efficiency of elastomers; curves of the electrical signal change; comparison of the strain sensor in sensing performances with other reports; the formula of the samples (molar ratios); and the summary of molecular design concepts and sensitivity of recently reported strain sensors (PDF)MIIT Key Laboratory of Critical Materials Technology for New Energy Conversion and Storage, School of Chemistry and Chemical Engineering, Harbin Institute of Technology, Harbin 150001, China; orcid.org/0000-0002-3711-5077; Phone: 86-451-8641-4806.; Email: jiangbo5981@hit.edu.cn; Fax: 86-451-8641-8270 Authors Xiangrong Shi − MIIT Key Laboratory of Critical Materials Technology for New Energy Conversion and Storage, School of Chemistry and Chemical Engineering, Harbin Institute of Technology, Harbin 150001, China Kuiyuan Zhang − MIIT Key Laboratory of Critical Materials Technology for New Energy Conversion and Storage, School of Chemistry and Chemical Engineering, Harbin Institute of Technology, Harbin 150001, China Liwei Zhao − MIIT Key Laboratory of Critical Materials Technology for New Energy Conversion and Storage, School of Chemistry and Chemical Engineering, Harbin Institute of Technology, Harbin 150001, China Yudong Huang − MIIT Key Laboratory of Critical Materials Technology for New Energy Conversion and Storage, School of Chemistry and Chemical Engineering, Harbin Institute of Technology, Harbin 150001, China Complete contact information is available at: https://pubs.acs.org/10.1021/acs.iecr.0c05238…”
mentioning
confidence: 99%
“…This was also because the impregnated epoxy resin had good corrosion resistance. Additionally, during the corrosion resistance test, we found that FUW also had a pH-response [ 32 ]. Under strong acidic and alkaline conditions, FUW appeared to be light yellow.…”
Section: Resultsmentioning
confidence: 99%
“…The self-healing of materials is a time-dependent process [99]. A crack in a material takes longer time to recover in its initial stage.…”
Section: Factors Affecting Self-healing With Nanomaterialsmentioning
confidence: 99%